2009
DOI: 10.3171/2009.2.spine08730
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological monitoring during surgery for cervical degenerative myelopathy and radiculopathy

Abstract: Object The objective of this systematic review was to use evidence-based medicine to examine the diagnostic and therapeutic utility of intraoperative electrophysiological (EP) monitoring in the surgical treatment of cervical degenerative disease. Methods The National Library of Medicine and Cochrane Database were queried using MeSH headings and key words relevant to cervical spine surgery and EP monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 28 publications
2
41
0
1
Order By: Relevance
“…6 Similar to lack of consensus for low-risk lumbar surgeries, there is not yet consensus supporting the use of IONM during low-risk cervical spine surgeries. 15 Indeed, our study showed no difference in independence at discharge between patients in whom IONM was used versus patients in whom IONM was not used during elective anterior cervical discectomy and fusion surgery. The absence of IONM use during low-risk cervical spine surgery is supported by other studies that have reported a lack of iatrogenic nerve and spinal cord injury among patients who underwent cervical spine surgery without use of IONM.…”
Section: Discussionmentioning
confidence: 90%
“…6 Similar to lack of consensus for low-risk lumbar surgeries, there is not yet consensus supporting the use of IONM during low-risk cervical spine surgeries. 15 Indeed, our study showed no difference in independence at discharge between patients in whom IONM was used versus patients in whom IONM was not used during elective anterior cervical discectomy and fusion surgery. The absence of IONM use during low-risk cervical spine surgery is supported by other studies that have reported a lack of iatrogenic nerve and spinal cord injury among patients who underwent cervical spine surgery without use of IONM.…”
Section: Discussionmentioning
confidence: 90%
“…1,11,15,19,34,42 Many developments have occurred since IOM was first used, 8 and currently SSEPs are used to assess the dorsal afferent tracts, 35 while MEPs are used for monitoring the motor tracts of the spinal cord. The utility and accuracy of each monitoring modality may be affected by the type of surgery, patient condition, anesthesia, and physiological changes during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,22,23,27,30,34,42 Signal changes such as increased latency (typically greater than 10% prolongation) and decreased amplitude (typically greater than 40% reduction) trigger concern for possible neurological injury, 25 yet these signal changes do not always correlate with the development of a postoperative deficit.…”
Section: -1118mentioning
confidence: 99%
“…Therefore, some surgeons would suggest early surgery for patients with CSM to ameliorate the risk of SCI. 2,9,19,21,22,24,27,33 However, there are insufficient data to correlate CSM with SCI, and whether the risk of SCI can be altered by surgical intervention remains elusive.…”
mentioning
confidence: 99%